ANALISIS PENGARUH KUALITAS PENERAPAN GOOD CORPORATE GOVERNANCE, LEVERAGE, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PERBANKAN DENGAN EARNINGS MANAGEMENT SEBAGAI VARIABEL INTERVENSI - Rifandi, Ahmad Candra; Bidayati, Utik (Jurnal Fokus Manajemen Bisnis, 2013)
This study aims to obtain empirical evidence about the influence ofÂ  the quality of the implementation of good corporate governance, leverage, and profitability of the banking firm value when intervention by earnings management. Quality of the implementation of good corporate governance is measured by a composite score of good corporate governance self assessment by Bank Indonesia Circular Letter No. 9/12/DNDP May 30, 2007, leverage measured by debt-to-equity ratio (DER), profitability measured by earnings growth, earnings management is measured by discreationary accruals, and firm value is measured by the ratio of price book value (PBV). Results of this study showed that the only significant effect of leverage on earnings management. While the quality of the implementation of good corporate governance and profitability no significant effect on earnings management. Earnings management had no significant effect on firm value, and thus the quality of the implementation of good corporate governance, leverage, and profitability does not affect the firm value when it intervened by earnings management.